Airway Epithelial Repair by a Prebiotic Mannan Derived from Saccharomyces cerevisiae - Christie F. Michael; Christopher M. Waters; Kim S. LeMessurier; Amali E. Samarasinghe; Chi Y. Song; Kafait U. Malik; D. Betty Lew (Journal of Immunology Research)
In asthmatic airways, repeated epithelial damage and repair occur. No current therapy directly targets this process. We aimed to determine the effects of mannan derived from S. cerevisiae (SC-MN) on airway epithelial wound repair, in vitro. The presence of functional mannose receptors in bronchial epithelial cells was shown by endocytosis of colloidal gold-Man BSA via clathrin-coated pits in 16HBE cells. In primary normal human bronchial epithelial cells (NHBEC), SC-MN significantly facilitated wound closure. Treatment with SC-MN stimulated cell spreading as indicated by a significant increase in the average lamellipodial width of wound edge 16HBE cells. In addition, NHBEC treated with SC-MN showed increased expression and activation of Krüppel-like factors (KLFs) 4 and 5, transcription factors important in epithelial cell survival and regulation of epithelial-mesenchymal transition. We conclude that SC-MN facilitates wound repair in human bronchial epithelium, involving mannose receptors.